2022
DOI: 10.1371/journal.pone.0266358
|View full text |Cite
|
Sign up to set email alerts
|

Potential complications of CAD/CAM-produced resin composite crowns on molars: A retrospective cohort study over four years

Abstract: Purpose Evaluation of the clinical performance of computer-aided design/computer-aided manufacturing-produced resin composite crowns (CAD/CAM composite crowns) on molars with a particular focus on placement location. Methods A retrospective cohort study was performed based on the clinical records of patients with CAD/CAM composite crowns on molars (June 2016 to March 2021). The hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated based the Cox proportional hazard model to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The initial concerns about the clinical necessity and suitability of CAD/CAM RBCs have already been addressed [ 21 , 22 ], and their functionality in the oral environment has been confirmed. The next development step was to expand the color and translucency portfolio in such a way that the CAD/CAM RBCs are in no way inferior to their light-curing counterparts in terms of aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…The initial concerns about the clinical necessity and suitability of CAD/CAM RBCs have already been addressed [ 21 , 22 ], and their functionality in the oral environment has been confirmed. The next development step was to expand the color and translucency portfolio in such a way that the CAD/CAM RBCs are in no way inferior to their light-curing counterparts in terms of aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical complications occurred in 29.3% of the 362 molar CADCAM resin crowns, of which 74.5% were debonding and 4.7% were fractures. Crown debonding of the molars most frequently occurred in the early stages, within the first 6 months 38 . The most common complications for composite crowns were a fracture of the crown and loss of retention for metal-ceramic crowns 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no www.nature.com/scientificreports/ prior studies have reported a relationship between PEEK and gingivitis, but PEEK has been reported to prevent bacterial adhesion 37 . Similar studies include retrospective cohort studies of metal-ceramic crowns and CAD/ CAM-produced resin composite crowns 38,39 . Clinical complications occurred in 29.3% of the 362 molar CAD-CAM resin crowns, of which 74.5% were debonding and 4.7% were fractures.…”
Section: Discussionmentioning
confidence: 99%
“…However, their applicability is hampered by the fact that it is difficult to achieve an adequate bonding with resin cements, with several studies reporting on clinical outcomes related to crown debonding [ 7 , 8 , 9 , 10 ]. The most recent study revealed that 362 CAD/CAM composite crowns were assessed over an average follow-up period of 378 d. Among these, 106 crowns exhibited clinical issues, with crown debonding accounting for 74.5% of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a relatively higher rate of debonding was observed in the post-fitting period. Furthermore, after the reattachment of the debonded crowns, only 16% of them (12 crowns) experienced subsequent debonding, while the rest remained intact for an extended period [ 7 ]. A similar pattern was reported by Kabetani et al, who found that 50% of debondings occurred within the first 4 months after cementation of CAD/CAM composite crowns.…”
Section: Introductionmentioning
confidence: 99%